Drivers of U.S. toxicological footprints trajectory 1998-2013 - Koh, S C L; Ibn-Mohammed, T; Acquaye, A; Feng, K; Reaney, I M; Hubacek, K; Fujii, H; Khatab, K (Scientific reports, 2016)
By exploiting data from the Toxic Release Inventory of the United States, we have established that the toxicological footprint (TF) increased by 3.3% (88.4 Mt) between 1998 and 1999 and decreased by 39% (1088.5 Mt) between 1999 and 2013. From 1999 to 2006, the decreasing TF was driven by improvements in emissions intensity (i.e. gains in production efficiency) through toxic chemical management options: cleaner production; end of pipe treatment; transfer for further waste management; and production scale. In particular, the mining sector reduced its TF through outsourcing processes. Between 2006 and 2009, decreasing TF was due to decrease in consumption volume triggered by economic recession. Since 2009, the economic recovery increased TF, overwhelming the influence of improved emissions intensity through population growth, consumption and production structures. Accordingly, attaining a less-toxic economy and environment will be influenced by a combination of gains in production efficiency through improvement in emissions mitigation technologies and changes in consumption patterns. Overall, the current analysis highlights the structural dynamics of toxic chemical release and would inform future formulation of effective mitigation standards and management protocols towards the detoxification of the environment.
Keywords: olovo; Environmental Monitoring; Climate Change; Lead; monitorování životního prostředí; látky znečišťující životní prostředí; skleníkový efekt; Greenhouse Effect; Models, Economic; Population Growth; látky znečišťující vzduch; hornictví; lidé; ekonomické modely; United States; Humans; populační růst; Waste Management; klimatické změny; Environmental Pollutants; Spojené státy americké; nakládání s odpady; Mining; Air Pollutants